HISTORICAL DEVELOPMENT IN THE DOCUMENTATION OF MARRIAGE CONTRACTS - Abdulwahhab Alshekh, Saad; Hj Abdullah, Raihanah; Samah, Mahamatayuding (Jurnal Syariah, 2019)
This study investigates the documentation of marriage contracts, beginning from the historical ages of Adam and Eve, peace be upon them, as manifested through the heavenly laws that Allah the Almighty had provided, the laws that were legislated by previous nations before our Prophet Muhammad (PBUH) was sent by Allah followed by the laws decreed by nations after Prophet Muhammad until the Iraqi Personal Status Law. In following the historical process of the documentation of marriage contracts, this study also looks at what was stated in the laws of heaven to see how a marriage contract was established. It looks at the reasons why a marriage contract had certain conditions omitted in the era of the Prophet Muhammad (PBUH), and as according to the Islamic law of that period. Specifically, this study aims to understand why Muslims only started documenting their marriage contracts more than two centuries after Hijrah. It also aims to understand what the legitimate policy was, followed by how the marriage contracts and registrations were performed in the Iraqi Personal Status Law. The statements of the contemporary jurists who considered documenting marriage certificates to be the jurisprudence era/ nawÄzil al-â€˜aá¹£r will be analyzed and evaluated. It is hoped that the analysis will be able to highlight the reasons showing why marriage certificates must be documented in accordance with the Islamic law and the civil law.